Further interceptions of the Neotropical fungus gnat Sciophila fractinervis Edwards, 1940 (Diptera, Mycetophilidae) in Britain with comments and observations on its biology and spread - Rob Deady; Mark Delaney; Eleanor Jones; Peter Chandler (Biodiversity Data Journal, 2022)
From 2020 onwards, several specimens of the Neotropical fungus gnat Sciophila fractinervis (Edwards, 1940) have been intercepted by Fera Science Ltd. on or near plant material in the United Kingdom originating from nurseries and glasshouses at four separate locations: Preston, Lancashire; Chichester, West Sussex; East Riding of Yorkshire; and Middlesbrough, North Yorkshire, as well as a single interception from the Netherlands. Gnat interceptions were associated with a wide range of plant species: Ficus benjamina, Ficus elastica, Dracaena reflexa var. angustifolia, Origanum vulgare, Rosmarinus officinalis, Thymus vulgaris, Impatiens hawkeri (Impatiens New Guinea hybrids), Chrysanthemum, as well as Fragaria vesca (var. Lusa). The species does not appear to be doing any damage to affected plants with growing conditions likely promoting multiplication under protection. The larvae likely feed on spores (generally saprophytic) adhering to webs they erect on the soil and around the base of plants with spores likely originating from the growing medium and plants. Their spread is likely facilitated by movement of the growing medium or plant material where pupae are suspended in the lower stem or leaf axils.An account of the various interceptions is provided, as well as images of the different life-stages with a brief discussion of Sciophila cincticornis Edwards, 1940, its relationship with Sciophila fractinervis and further evidence of instability in vein R2+3 in the Sciophila genus.